Comparison of microleakage under orthodontic brackets bonded with five different adhesive systems: in vitro study - Nela Masarykova; Emil Tkadlec; Zdenek Chlup; Jan Vrbsky; Alena Brysova; Pavlina Cernochova; Lydie Izakovicova Holla (BMC, 2023)
Abstract Background Orthodontic treatment is associated with numerous adverse side effects, such as enamel discoloration, demineralization or even caries. The presence of microleakage between the enamel and the adhesive and between the adhesive and the base of the orthodontic bracket allows penetration of the bacteria, molecules, and liquids into the enamel and can lead to unpleasant "white spot lesions" or secondary caries beneath and around the brackets. The aim of this in vitro study was to evaluate microleakage in five adhesive systems commonly used in orthodontic practice for bonding brackets. Methods One hundred extracted premolars were divided into five groups of twenty teeth. Stainless steel Legend medium metal brackets were bonded to teeth using five adhesive systems: resin-reinforced glass ionomer cement GC Fuji Ortho LC (GCF) and composite materials Light Bond (LB), Transbond XT (TB), Trulock™ Light Activated Adhesive (TL), and GC Ortho Connect (GCO). The specimens were subjected to thermal cycling, stained with 2% methylene blue, sectioned with low-speed diamond saw Isomet and evaluated under a digital microscope. Microleakage was detected at the enamel-adhesive and adhesive-bracket interfaces from occlusal and gingival margins. Statistical analysis was performed using generalized linear mixed models with beta error distribution. Results Microleakage was observed in all materials, with GCF showing the highest amount of microleakage. Composite materials GCO, TB, and LB exhibited the lowest amount of microleakage with no statistical difference between them, while TL showed a statistically significantly higher amount of microleakage (p < 0.001). The enamel-adhesive interface had more microleakage in all composite materials (GCO, LB, TB, and TL) than the adhesive bracket-interface (p < 0.001). The highest amount of microleakage occurred in the gingival region in all materials. Conclusion Composite materials showed better adhesive properties than a resin-reinforced glass ionomer cement. The presence of microleakage at the enamel-adhesive interface facilitates the penetration of various substances into enamel surfaces, causing enamel demineralization and the development of dental caries.